IMPLEMENTATION OF VR AUTOMOTIVE WORKSHOP ON MOOC AS AN ACTUALIZATION OF PROSSER’S FIRST PRINCIPLE FOR TRAINING INDUSTRY-STANDARD AUTOMOTIVE EQUIPMENT - Mindarta, Erwin Komara; Rudiyanto, Eddy; Juharyanto, Juharyanto (Faculty of Administrative Science, Universitas Brawijaya, 2025)
The growing disparity between vocational education and industry standards, particularly in the automotive sector, has prompted the search for innovative training solutions that provide authentic, accessible, and engaging learning environments. This study aims to develop and evaluate a Virtual Reality-based Automotive Workshop integrated into a Massive Open Online Course platform as a means to simulate industry-standard automotive procedures and operational environments. Using a mixed-methods design, the research involved pretest and posttest assessments, structured observations, user perception surveys, and expert validation. Participants consisted of vocational students and trainees who completed interactive VR training modules embedded in a self-paced online course. The instructional model followed the ADDIE development framework, ensuring alignment with pedagogical principles and industry practices. Findings revealed a significant improvement in learners’ technical competencies, as reflected in increased posttest scores and moderate-to-high learning gains. Observational data showed high task completion rates and procedural accuracy, while user responses indicated strong motivation and satisfaction with the VR experience. Expert reviewers confirmed the simulation’s fidelity and relevance to real-world automotive contexts. These results suggest that immersive digital environments can replicate industry-relevant tasks, support procedural mastery, and enhance learner engagement. The integration of VR and online platforms also extends the reach of vocational education, particularly for institutions with limited access to physical workshops. This study contributes to the evolving landscape of digital vocational education by demonstrating how immersive simulations grounded in pedagogical theory can strengthen workforce readiness. The findings support the application of authentic, context-rich learning environments to improve educational outcomes and reduce the skills gap in technical fields.